Login
Remember
Register
Home
All Activity
Q&A
Questions
Hot!
Unanswered
Tags
Categories
Users
Ask a Question
Ask a Question
Show that. `(4pq + 3q)^2 – (4pq – 3q)^2 =
0
votes
asked
Jan 17, 2022
in
8th-maths
by
Simran
(
1.8k
points)
Show that.
`(4pq + 3q)^2 – (4pq – 3q)^2 = 48pq^2`
marks2
chapter9
#sub
Please
log in
or
register
to answer this question.
0
Answers
Categories
All categories
Maths
(8.6k)
12th-maths
(0)
11th-maths
(0)
10th maths
(0)
9th-maths
(0)
8th-maths
(8.6k)
Science
(14)
Physics
(3.4k)
Related questions
Show that. `(4pq + 3q)^2 – (4pq – 3q)^2 =
Show that. `(4pq + 3q)^2 – (4pq – 3q)^2 =
Find the value of a, if `pq^2a = (4pq + 3q)^2 – (4pq –
Find the value of a, if `pq^2a = (4pq + 3q)^2 – (4pq –
Find the value of a, if `pq^2a = (4pq + 3q)^2 – (4pq –